Discovery of novel tripeptide propylene oxide proteasome inhibitors for the treatment of multiple myeloma. (15th June 2021) - Zhang, Wen; Wang, Xueyuan; Zhang, Haoyang; Wen, Tiantian; Yang, Lin; Miao, Hang; Wang, Jia; Liu, Hailong; Yang, Xu; Lei, Meng; Zhu, Yongqiang
Graphical abstract: Abstract: The ubiquitin proteasome pathway (UPP) plays a critical role in the maintenance of cell homeostasis and the development of diseases, such as cancer and neurodegenerative disease. A series of novel tripeptide propylene oxide compounds as proteasome inhibitors were designed, synthesized and biologically investigated in this manuscript. The enzymatic activities of final compounds against 20S human proteasome were investigated and structure-activity relationship (SAR) was summarized. Some potent compounds were further evaluated to inhibit the proliferation of multiple myeloma (MM) cancer cell lines RPMI8226 and U266B. The results showed that some compounds were active against MM cancer cell lines with IC50 values of less than 50 nM. The microsomal metabolic stabilities in human, rat and mice species were carried out and the results showed that compounds 30 and 31 were stable enough to be in vivo investigated. The in vivo pharmacokinetic results showed that compounds 30 and 31 had acceptable biological parameters for both ig and iv administrations. In vivo antitumor activities of compounds 30 and 31 with the doses of 100 mg/kg and 50 mg/kg BIW were performed by using RPMI8226 xenograft nude mouse model. Toxicities of compounds 30 and 31 were not observed during the experiment and dose dependent effect was obvious and the tumor volume was greatly inhibited.